Generators for the semigroup of endomorphisms of an independence Algebra - Araújo, João (2015)
Given an independence algebra A of infinite rank, we denote the endomorphism monoid and the automorphism group of A by End(A)and Aut(A) respectively. This paper is concerned with finding minimal subsets R of End(A) such that Aut(A) [ E(End(A)) [ R is a generating set for End(A), where E(End(A)) denotes its set of idempotents.